Perilaku Memilih Umpan Dengan Fagostimulan Yang Berbeda Pada Kecoak Jerman Blattella germanica L. (Dictyoptera: Blattellidae) - Aliefia, Rizky Arjunnajat; Ambarningrum, Trisnowati Budi; Basuki, Edi (Fakultas Biologi Universitas Jenderal Soedirman, 2020)
German cockroach (Blattella germanica L.) is one of the important residential pest insects, because of its role as a vector of disease. To reduce its population, it can be used with bait techniques. However, there was a rejection of glucose against German cockroaches against phagostimulant-based commercial bait. Therefore it is necessary to review the phagostimulant as a component of the bait to minimize failure to control German cockroaches based on bait using German cockroaches strain VCRU (Vector Control Research Unit). The first step to formulating the bait is to find the phagostimulant most sought by German cockroaches. The ingredients used as fagostimlan are sugar, durian, erythritol, and banana. The purpose of this study was to determine the behavior of choosing German cockroaches against bait with different phagostimulants and the peak of feeding activity in German cockroaches. This study used an experimental method with a Completely Randomized Design (CRD) consisting of 4 treatments giving phagostimulant and repeated 4 times divided into four test arenas. The treatment consisted of bait which each contained sugar, durian, erythritol, and banana as phagostimulants. Observation of behavior using the method of behavior sampling is recorded in continuous recording for 24 hours using a Closed Circuit Television (CCTV) camera. The parameters measured were latency, frequency, duration, and peak feeding activity of German cockroaches. The data were analyzed with ANOVA at p <0.05. The results showed that the behavior of selecting cockroaches from the VCRU strain on the bait was not significantly different (p<0.05) and was attracted to all feeds provided, but gel bait with sugar phagostimulant was the preferred bait by looking at the three parameters of latency, frequency, and duration. The results of the average latency in the VCRU strain to the durian gel for 17 minutes, the average frequency of most visits to the sugar gel in the VCRU strain by 10 times, the longest average duration of the VCRU strain gel for 1 minute 46 seconds and peak eating activity VCRU strains occur between 17:00 - 20:00.